Neurologists’ Openness to Evidence-Based Innovation in Multiple Sclerosis Care: Individual and Structural Determinants - Monreal E; Gómez-Ballesteros R; Meca-Lallana V; Caminero AB; Meca-Lallana JE; Martínez-Yélamos S; Landete L; García-Domínguez JM; Agüera E; García-Arcelay E; Medrano N; Villar LM; et al. (Neuropsychiatric Disease and Treatment)
Enric Monreal,1 Rocío Gómez-Ballesteros,2 Virginia Meca-Lallana,3 Ana B Caminero,4 Jose E Meca-Lallana,5 Sergio Martínez-Yélamos,6 Lamberto Landete,7 Jose M García-Domínguez,8 Eduardo Agüera,9 Elena García-Arcelay,2 Nicolas Medrano,2 Luisa M Villar,10 Jorge Maurino2 1Department of Neurology, Hospital Universitario Ramón y Cajal, Madrid, Spain; 2Medical Department, Roche Farma, Madrid, Spain; 3Department of Neurology, Hospital Universitario La Princesa, Madrid, Spain; 4Department of Neurology, Complejo Asistencial de Ávila, Ávila, Spain; 5Department of Neurology, Hospital Clinico Universitario Virgen de la Arrixaca, Murcia, Spain; 6Department of Neurology, Hospital Universitari de Bellvitge, Barcelona, Spain; 7Department of Neurology, Hospital Universitario Dr. Peset, Valencia, Spain; 8Department of Neurology, Hospital Universitario Gregorio Marañón, Madrid, Spain; 9Department of Neurology, Hospital Universitario Reina Sofía, Córdoba, Spain; 10Department of Immunology, Hospital Universitario Ramón y Cajal, Madrid, SpainCorrespondence: Jorge Maurino, Medical Department, Roche Farma, Ribera del Loira 50 (28042), Madrid, Spain, Tel +34 91 324 8100, Email jorge.maurino@roche.comPurpose: Integration of evidence-based innovations, such as serum neurofilament light chain (sNfL) measurement into routine practice represents a pivotal opportunity to advance personalized care in multiple sclerosis (MS) management. This study assessed neurologists’ openness to adopting healthcare innovations (sNfL testing), focusing on individual characteristics and structural factors like workplace environment and resources.Methods: An observational, cross-sectional study was conducted in partnership with the Spanish Society of Neurology. Neurologists caring for patients with MS completed an e-survey assessing openness to innovation using the Openness subscale of the Evidence-Based Practice Attitude Scale (EBPAS), alongside measures of empathy, healthcare-related regret, risk preferences, burnout, and workplace communication. Logistic and linear regression models were conducted to identify predictors of openness to innovation.Results: One hundred and sixteen neurologists were studied. Mean age (SD) was 41.9 (10.1) years, 53.4% were male. Mean experience as neurologists was 16.0 (9.2) years and 96.6% worked in an academic hospital. Median (IQR) EBPAS-Openness score was 3.0 (2.5– 3.5), with 54.3% (n=63) of participants demonstrating openness to innovation. Participants fully dedicated to MS care, managing higher patient volumes, engaged in research publications, with access to serum neurofilament light chain testing, and a greater propensity for risk-taking, were more open to adopting innovations than their counterparts. Multivariate logistic regression analysis showed that access to sNfL testing and higher empathy levels were significant predictors of openness (OR=3.52, CI 95%: 1.3– 10.3; p=0.016 and OR=1.09, CI 95%: 1.0– 1.2; p=0.005, respectively). Complementary linear regression reinforced the significant positive association between higher EBPAS-Openness scores and empathy (estimate=0.024, p=0.001).Conclusion: Neurologists exhibited a varied openness to innovation. Implementing initial innovative strategies in clinical practice should prioritize neurologists with specific profiles to support the integration of emerging tools and personalized healthcare approaches in MS care.Keywords: innovation, multiple sclerosis, decision-making, neurofilament light chain, personalized medicine